Whole genome characterization and diagnostics of prunus necrotic ringspot virus (PNRSV) infecting apricot in India - Md Salik Noorani; Mirza Sarwar Baig; Jawaid Ahmad Khan; Alam Pravej (Scientific Reports, 2023)
Abstract Prunus necrotic ringspot virus (PNRSV) is a pathogen that infects Prunus species worldwide, causing major economic losses. Using one and two-step RT-PCR and multiplex RT-PCR, the whole genome of the PNRSV-infecting apricot was obtained and described in this study. Computational approaches were used to investigate the participation of several regulatory motifs and domains of the Replicase1, Replicase2, MP, and CP. A single degenerated reverse and three forward oligo primers were used to amplify PNRSV’s tripartite genome. The size of RNA1 was 3.332 kb, RNA2 was 2.591 kb, and RNA3 was 1.952 kb, according to the sequencing analysis. The Sequence Demarcation Tool analysis determined a percentage pair-wise identity ranging between 91 and 99% for RNA1 and 2, and 87–98% for RNA3. Interestingly, the phylogenetic analysis revealed that closely related RNA1, RNA2, and RNA3 sequences of PNRSV strains from various geographical regions of the world are classified into distinct clades or groups. This is the first report on the characterization of the whole genome of PNRSV from India, which provides the cornerstone for further studies on the molecular evolution of this virus. This study will assist in molecular diagnostics and management of the diseases caused by PNRSV.